Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1088/0268-1242/16/10/102
|View full text |Cite
|
Sign up to set email alerts
|

Ion-beam-induced isolation of GaAs layers by4He+implantation: effects of hot implants

Abstract: The formation of thermally stable highly resistive regions in n-type GaAs layers during helium ion bombardment at elevated temperatures, where dynamic annealing of radiation-induced defects is substantial, was investigated and presented here. The substrate temperatures were chosen to be room temperature (RT), 100 and 200 • C. Semi-insulating GaAs wafers of (100) orientation were implanted with multi-energy 29 Si atoms to create a flat dopant distribution of about 0.7 µm in thickness. A uniform damage density w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[7][8][9][10][11][12][13] Most of those studies have been driven by the need to enhance the current understanding of the physical mechanisms that underlie defect isolation. The results from the comprehensive investigation of de Souza and coworkers [7][8][9][10] suggest that antisite defects created by replacement collisions and/or their defect complexes are responsible for free carrier trapping in GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Most of those studies have been driven by the need to enhance the current understanding of the physical mechanisms that underlie defect isolation. The results from the comprehensive investigation of de Souza and coworkers [7][8][9][10] suggest that antisite defects created by replacement collisions and/or their defect complexes are responsible for free carrier trapping in GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…Ion irradiation is a well‐established technique for tuning various physical, electrical, optical and mechanical properties of these materials. For example, ion irradiation and subsequent annealing can produce modified layers (both on the surface and deep inside the target) with their electrical conductivity different from that of the surrounding matrix . In case of semiconductors, these energetic irradiated ions produce various types of defects, like vacancies and interstitials, along their path.…”
Section: Introductionmentioning
confidence: 99%
“…He, O or B) to create highly resistive regions [14]. A number of studies have been performed on the use of He implantation in GaAs to create highly resistive regions [15,16]. In these studies it was shown that high resistive regions are formed through the creation of deep 'mid-band' traps which restrict the flow of charge.…”
Section: Introductionmentioning
confidence: 99%
“…For example Oxygen implantation into InGaAs results in resistances in the range 10 4 -10 5 /Square [16], while Iron and Krypton implantation have both been used to increase the sheet resistance a further order of magnitude to 10 6 /Square [19]. Additionally investigation of proton implantation in InSb has been shown to result in n-type material becoming p-type, due to traps not being created in the middle of the bandgap [17].…”
Section: Introductionmentioning
confidence: 99%